Modelling of the Production Process in the Macroeconometric Model W8D-2010 - Florczak, Waldemar; Świeczewska, Iwona; Welfe, Władysław (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
This article presents the main aspects related to the modeling of the production process in the simulation model W8D-2010 for the Polish economy. The neoclassical production function adopted in this model assumes full utilization of the production factors. This means that the starting point for estimating the value of potential output induces comprehensive explanation of changes in the production factors: labor, capital and the changes in technology. Technology is represented by changes in the total factor productivity (TFP). The main determinants of TFP changes are stocks of the knowledge and human capital, as well as the stocks of knowledge transferred from abroad with respect to various channels of this transfer.